An evaluation of HHV-6 as an etiologic agent in Hodgkin lymphoma and brain cancer using IARC criteria for oncogenicity - Michael J. Wells; Steven Jacobson; Paul H. Levine (Infectious Agents and Cancer, 2019)
Abstract Background Human herpesvirus-6 (HHV-6) is a ubiquitous double-stranded DNA virus that can cause roseola infantum, encephalitis, and seizure disorders. Several studies have shown an association between HHV-6 and cancer but confirmation of an etiologic role is lacking. We reviewed the criteria for viral causation of cancer used by The International Agency for Research on Cancer (IARC) for six oncogenic viruses and applied criteria to published reports of HHV-6 and its association with Hodgkin lymphoma and brain tumors. Methods Our major criteria for oncogenicity were finding evidence of the virus in every tumor cell and prevention of the tumor by an antiviral vaccine. Our six minor criteria included: 1) suggestive serologic correlation, such as higher virus antibody levels in cases compared to controls; 2) evidence of the virus in some but not all tumor cells, and 3) time space clustering. We focused on Epstein-Barr virus (EBV) as the primary virus for comparison as HHV-6 and EBV are both Herpesviridae, ubiquitous infections, and EBV is well-accepted as a human oncovirus. Particular attention was given to Hodgkin lymphoma (HL) and brain cancer as these malignancies have been the most studied. Results No studies reported HHV-6 satisfying either of the major criteria for oncogenicity. Of the minor criteria used by IARC, serologic studies have been paramount in supporting EBV as an oncogenic agent in all EBV-associated tumors, but not for HHV-6 in HL or brain cancer. Clustering of cases was suggestive for both HL and brain cancer and medical intervention suggested by longer survival in patients treated with antiviral agents was reported for brain cancer. Conclusion There is insufficient evidence to indicate HHV-6 is an etiologic agent with respect to HL and brain cancers. We suggest that methods demonstrating EBV oncogenicity be applied to HHV-6. It is important that one study has found HHV-6 in all cancer cells in oral cancer in a region with elevated HHV-6 antibodies and therefore HHV-6 can still be considered a possible human oncogenic virus.